An in vitro model of the glomerular capillary wall using electrospun collagen nanofibres in a bioartificial composite basement membrane. - Sadie C Slater; Vince Beachley; Thomas Hayes; Daming Zhang; Gavin I Welsh; Moin A Saleem; Peter W Mathieson; Xuejun Wen; Bo Su; Simon C Satchell (PLoS ONE)
The filtering unit of the kidney, the glomerulus, contains capillaries whose walls function as a biological sieve, the glomerular filtration barrier. This comprises layers of two specialised cells, glomerular endothelial cells (GEnC) and podocytes, separated by a basement membrane. Glomerular filtration barrier function, and dysfunction in disease, remains incompletely understood, partly due to difficulties in studying the relevant cell types in vitro. We have addressed this by generation of unique conditionally immortalised human GEnC and podocytes. However, because the glomerular filtration barrier functions as a whole, it is necessary to develop three dimensional co-culture models to maximise the benefit of the availability of these cells. Here we have developed the first two tri-layer models of the glomerular capillary wall. The first is based on tissue culture inserts and provides evidence of cell-cell interaction via soluble mediators. In the second model the synthetic support of the tissue culture insert is replaced with a novel composite bioartificial membrane. This consists of a nanofibre membrane containing collagen I, electrospun directly onto a micro-photoelectroformed fine nickel supporting mesh. GEnC and podocytes grew in monolayers on either side of the insert support or the novel membrane to form a tri-layer model recapitulating the human glomerular capillary in vitro. These models will advance the study of both the physiology of normal glomerular filtration and of its disruption in glomerular disease.